A case report of agoraphobia following right parietal lobe surgery: changes in functional and structural connectivities of the multimodal vestibular network - Indovina, Iole; Cacciola, Alberto; Delle Monache, Sergio; Milardi, Demetrio; Lacquaniti, Francesco; Toschi, Nicola; Cochereau, Jerome; Bosco, Gianfranco (Frontiers in Neurology, 2023)
Agoraphobia is a visuo-vestibular-spatial disorder that may involve dysfunction of the vestibular network, which includes the insular and limbic cortex. We sought to study the neural correlates of this disorder in an individual who developed agoraphobia after surgical removal of a high-grade glioma located in the right parietal lobe, by assessing pre- and post-surgery connectivity in the vestibular network. The patient underwent surgical resection of the glioma located within the right supramarginal gyrus. The resection interested also portions of the superior and inferior parietal lobe. Structural and functional connectivity were assessed through magnetic resonance imaging before, 5 and 7 months after surgery. Connectivity analyses focused on a network comprising 142 spherical regions of interest (4 mm radius) associated with the vestibular cortex, 77 in the left and 65 in the right hemisphere (excluding lesioned regions). Tractography for diffusion weighted structural data and correlation between timeseries for functional resting-state data were calculated for each pair of regions in order to build weighted connectivity matrices. Graph theory was applied to assess post-surgery changes in network measures, such as strength, clustering coefficient and local efficiency. Structural connectomes after surgery showed a decrease of strength in the preserved ventral portion of the supramarginal gyrus (PFcm) and in a high order visual motion area in the right middle temporal gyrus (37dl), and decrease of the clustering coefficient and of the local efficiency in several areas of the limbic, insular cortex, parietal and frontal cortex, indicating general disconnection of the vestibular network. Functional connectivity analysis showed both a decrease of connectivity metrics, mainly in high order visual areas and in the parietal cortex, and an increase of connectivity metrics, mainly in the precuneus, parietal and frontal opercula, limbic and insular cortex. This post-surgery reorganization of the vestibular network is compatible with altered processing of visuo-vestibular-spatial information, yielding to agoraphobia symptoms. Specifically, post-surgical functional increases of clustering coefficient and local efficiency in the anterior insula and in the cingulate cortex might indicate a more predominant role of these areas within the vestibular network, which could be predictive of the fear and avoiding behavior characterizing agoraphobia.